Modeling of anisotropic hardening and grain size effects based on advanced numerical methods and crystal plasticity - Berisha, B.; Hirsiger, S.; Hippke, H.; Hora, P.; Mariaux, A.; Leyvraz, D.; Bezençon, C. (Archives of Mechanics, 2019)
Modeling of anisotropic behavior as well as hardening behavior based on micromechanical quantities in combination with a spectral solver is the focus of this study. A deep drawing steel as well as two different aluminum alloys are investigated. Prediction capabilities of the proposed modeling strategy are discussed and the benefits of the micromechanical model are highlighted. Further, a comparison of the crystal plasticity (CP) results with the well established macroscopic model YLD2000-2d underlines the importance of the CP as a complementary modeling technique to the macroscopic modeling. Both models – the microscopic as well as the macroscopic – are validated on experimental data mainly gained from uniaxial and biaxial tests. In the second part of this study, strong inhomogeneous microstructures are investigated from a modeling point of view. For this purpose, a Hall–Petch phenomenological model is implemented in the CP open-source code DAMASK to take the grain size effects into account. Appropriate combinations of the grain sizes in a bimodal microstructure are presented in order to increase the strength as well as ductility of a generic aluminium alloy. The proposed numerical strategy of coupling the CP and efficient FFT-based spectral solver supports the development of new materials in an optimal way.